Region-specific changes in Mus musculus brain size and cell composition under chronic nutrient restriction - Barbeito Andrés, Jimena (2019)
Nutrition is one of the most influential environmental factors affecting the development of different tissues and organs. It is suggested that under nutrient restriction the growth of the brain is spared as a result of the differential allocation of resources from other organs. However, it is not clear whether this sparing occurs brain-wide. Here, we analyzed morphological changes and cell composition in different regions of the offspring mouse brain after maternal exposure to nutrient restriction during pregnancy and lactation. Using highresolution magnetic resonance imaging, we found that brain regions were differentially sensitive to maternal protein restriction and exhibited particular patterns of volume reduction. The cerebellum was reduced in absolute and relative volume, while cortex volume was relatively preserved. Alterations in cell composition (examined by the isotropic fractionator method) and organization of white matter (measured by diffusor tensor images) were also region specific. These changes were not related to the metabolic rate of the regions and were only partially explained by their specific growth trajectories. This study is a first step towards understanding the mechanisms of regional brain sparing at microstructural and macrostructural levels resulting from undernutrition.